Persistent Left Superior Vena Cava Draining into Left Atrium as a Cause of Persistent Systemic Desaturation after Surgery. Issue 3 (23rd December 2013) - Agarwal, Ashish; K.S., Ravindranath; Agrawal, Navin; Patra, Soumya; Agarwal, Neena; Manjunath, C.N.
<x xml:space="preserve">Abstract</x> Persistent left superior vena cava (LSVC) is a rare congenital anomaly which usually produces no physiologic derangements if it drains into the right atrium via the coronary sinus, but it may cause significant desaturation when it drains into the left atrium (LA). Failure to diagnose LSVC communicating with the LA preoperatively may lead to serious consequences. We are describing an interesting case of a boy who presented with systemic desaturation due to an undetected LSVC after having undergone corrective surgery for atrioventricular canal defect. We have demonstrated that echocardiography with agitated saline contrast is a simple, accurate, and inexpensive diagnostic modality.